Straw return decreases N surface runoff losses in croplands: Evidence from a global meta-analysis - Xinyi Shi; Liangping Wu; Jing Xiang; Hongxu Liang; Ruibo Sun; Yusef Kianpoor Kalkhajeh; Zhi Wang; Heng Fang; Chao Ma (Agricultural Water Management)
Agricultural non-point source pollution, caused by Nitrogen (N) surface runoff losses, threatens green development and rural environmental quality. Straw return could reduce N losses by improving soil structure and N retention. However, the impact of straw return on N losses from paddy and upland fields in croplands is not well-resolved due to differences in environmental and agronomic management factors. Herein, we conducted a meta-analysis using 75 publications to evaluate the effects of straw return on N surface runoff losses, total N concentration, and surface runoff volume from paddy and upland fields. The results revealed that straw return significantly decreased N runoff by an average of 18.12 % (P < 0.05), with 1.56 and 24.54 % reductions from paddy and upland fields, respectively, compared with non-straw amended fields. Furthermore, straw return caused significant decreases of 15.5 and 40.54 % in paddy N concentration and upland runoff volume, respectively. The impacts of straw return on N runoff properties vary with the environmental and agronomic management factors. In paddy fields, the primary determinants are the average annual temperature (MAT), average annual precipitation (MAP), and the straw return method. In uplands, the primary factors affecting N runoff properties are soil total N (TN), soil acidity and alkalinity, N application rate (NAR), straw application amount (SAR), and the straw return method. This study provides a reference for the decision-makers and stakeholders to effectively reduce N losses via straw return in global croplands.